ANALISIS PERILAKU STRUKTUR BETON DAN BAJA DENGAN METODE LEVELLING TIME HISTORY (STUDI KASUS GEDUNG E ITERA, LAMPUNG, INDONESIA) - Ahmad Yudi; Bayzoni M.T.; Nugraha Bintang Wirawan; Rijuli Nadaek (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2019)
The selection of structural material types can be based on analyzing the behavioral of the structure by giving a nonlinear dynamic earthquake load of time history. Because in Indonesia doesn’t have any data of time history record, it is necessary to match the time history data with the design spectrum response. Gedung E ITERA is modeled on reinforced concrete structures and steel structures with open frame models for the same as built drawing. Then can be evaluated the structural behavior that is like mass participation, plastic design, displacement, rotation, and base shear with time history load that will be levelling (levelling time history). With levelling the time history load , it can be found the first structural part that collapses and the maximum load that can be retained by the structure for one of the mitigation effort. The analysis uses a nonlinear dynamic time history analysis with the most dominant combination is earthquake combination. The results of this study show the differences in structural performance, the location of structural failure, and the maximum load that can be retained by the reinforced concrete structure and steel structure of gedung E Itera.